Giving back to the community through maths education outreach programme - Karim, Mariathy; Hilmi, Zulkifli Ab Ghani (Universiti Teknologi MARA, 2009)
Apart from teaching, researching and publishing, giving back to communities from which we come from in the form of community services and outreach programmes has also been regarded as one of the lecturers' Annual Targeted Task (Sasaran Kerja Tahunan). This paper highlights the latest community service programme of the Maths & Statistics Department, a two session Maths Clinic for students of Sekolah Menengah Teknik Puteri. The benefits were not just about the students achieving good grades in the SPM maths paper but more importantly, the forging of bonds between all those involved, the feeling of social connectedness, the increase sense of social responsibilities and the impact of UiTM Pahang's presence within the surrounding communities.